Arquitetura de ruínas: delírio e devaneio na construção do espaço trágico em lavoura arcaica - (:unkn) unknown (Universidade Federal de Goiás, 2014)
This work lends itself to joint analysis of two corpora: the novel “Lavoura Arcaica” writer Raduan Nassar, and his eponymous film, produced by Director Luiz Fernando Carvalho. The analysis of the book it is guided in the study of space, according to the postulates of the “Poetics of space”, the philosopher and theorist of imagination Gaston Bachelard, with emphasis on the concepts of topophilia and topophobia and of his work. Still based in phenomenology bachelardian, now under the foundations of the “Poetics of Reverie”, emphasis will be given to the Word as one of the veins of the narrative, conductors the book reveals the tone of poetic speech, as the hits of reverie or loathing of the protagonist. Under another view, memory and identity, join the rave and daydream for together, appear as constituent elements of the stream of consciousness that pervades the whole plot. With regard to the analysis of the film Lavoura Arcaica, cinematic space emerges as filmic diegetic element to be analyzed under the focus of the studies undertaken by narratologics André Gaudreault and François Jost. The aim is to understanding how film sensitive construction occurs in the cinematic image. Synesthesia and influences of the Expressionist movement are portrayed as structural elements and stylistic in some scenes. The space as emotional and memory synesthetic reconstruction, justifying distortions, unfocused and deletions of/on the image to transmit all existential crisis experienced by the protagonist of the story, tragic narrative that make both the novel and the film true masterpieces national literature and Cinema.
Keywords: Literatura; Cinema; Espaço; Devaneio; Expressionismo; Literature; space; Reverie; Expressionism; LETRAS::LINGUA PORTUGUESA